Prolonged use of pegylated liposomal doxorubicin in gynecologic malignancies - S. Yost; J.L. Konal; A.V. Hoekstra (Elsevier, 2019)
Pegylated liposomal doxorubicin (PLD) is a palliative treatment option for patients with recurrent gynecologic malignancies. It has an appealing toxicity profile and responses can be prolonged. There is no consensus as to the level of cardiac toxicity. Current label warnings, National Comprehensive Cancer Network (NCCN) guidelines, and extrapolation of prescribing guidelines from doxorubicin, may limit PLD's use in patients with baseline cardiac comorbidities, limit the lifetime dosing of an effective palliative treatment, or lead to over-use of unnecessary cardiac testing. This case series describes the experience of 18 patients using prolonged courses of PLD for gynecologic malignancies with no cardiac toxicity. Keywords: Pegylated liposomal doxorubicin, Cardiac toxicity, Palliative, Prolonged